GE_GERICHTE C/11062/2016 vom 19. Dezember 2016 - GE Cour de justice (2016)
CAS CLAIR ; EXPULSION DE LOCATAIRE ; CONTESTATION DU CONGÉ ; DEMEURE ; SURSIS CONCORDATAIRE ; SUSPENSION DE LA PROCÉDURE | CPC.257; CO. 257d; CP.293c